How does the tennis serve technique influence the serve-and-volley? - Martin, C.; Bideau, B.; Nicolas, G.; Delamarche, P.; Kulpa, R. (Journal of Sports Sciences, 2012)
In tennis, a high ball velocity and a fast run toward the net are key features to successful performance of "serve-and-volley" players. For the serve, tennis players can use two techniques: the foot-up (FU) or foot-back (FB) technique. The aim of this study was to determine if the running time toward the net after the serve and the ball velocity (Vball) vary between these two techniques. Moreover we analysed the angular momentum values of the trunk and of the arm holding the racquet. Fifteen expert tennis players performed six successful serve-and-volleys with both techniques. Running time to the net is significantly lower for FB, whereas Vball is significantly higher for FU. Trunk and arm angular momentums about the transverse axis are significantly higher with FU before ball impact. A significant correlation (r = 0.81, P < 0.001) exists between changes in the maximal trunk angular momentum and in running time to the net between the two serve techniques. A significant correlation (r = 0.84, P < 0.001) also exists between changes in the maximal trunk angular momentum and in Vball between the two serve techniques. According to these results, FB is the best technique for moving as quickly as possible to the net because of a lower trunk angular momentum.